MetOda Penentuan Nitrit Trace di Lingkungan Perairan sebagai Kompleks 4-(4-Nitrobenzenao)-1-Aminonaftalen Secara Ekstraksi N-Amil Alkohol-Spektrofotometri - Choirul Amri (Sanitasi: Jurnal Kesehatan Lingkungan, 2008)
A study of extraction-spectrophotometric method for the determination of trace nitriteas 4-(4-nitrobenzenazo)-1-aminonaphthalene complex using n-amylalcohol as organic solventshas been conducted.Results of the study showed that extraction-spectrophotometric determination of nitriteusing n-amylalcohol had high sensitivity and low limit of detection. This method produced linearconcentration of 0.000 - 0.054 mg/l NO2—N; detection limit of 2.09x10-4 mg/l NO2—N; andsensitivity of 34.514 ± 0.398 absorbance unit per mg/l of NO2--N.